Productivity of pigs fed with solid-state fermented apple pomace and an enzymatic complex - Chamorro-Ramírez, Francisco Héctor; García-Macías, José Arturo; Durán-Meléndez, Lorenzo Antonio; Peña-González, Esmeralda Mónica; González-Sánchez, José Fernando (Ecosistemas y Recursos Agropecuarios, 2017)
The productive performance of pigs fed with solid-state fermented apple pomace (FAP) and an enzy- matic complex (ENZ) was evaluated. Twenty-four Landrace x York (38.9 ± 3.6 kg) pigs were fed ad libitum with di erent diet treatments including FAP and ENZ: T0-0 (0 g kg−1 FAP - 0 g kg−1 ENZ), T0-1 (0 g kg−1 FAP + 1 g kg−1 ENZ), T50-0 (50 g kg−1 FAP + 0 g kg−1 ENZ), T50-1 (50 g kg−1 FAP + 1 g kg−1 ENZ), T100-0 (100 g kg−1 FAP + 0 g kg−1 ENZ) and T100-1 (100 g kg−1 FAP + 1 g kg−1 ENZ). Productivity; Feed intake, F:G ratio, Weight gain, return on investment by monetary unit (pro tability index, PI) and carcass traits; Carcass dressing percent and primary cuts, were evaluated. Data were analyzed according to the randomized complete block design. Productivity and feeding characteristics were not a ected by FAP or ENZ (p > 0.05). Hot dressing percent was a ected by ENZ (p = 0.0497). T100-0 and T100-0 showed similar (p > 0.05) value to T0-0. Primary cut yield was not negatively a ected (p > 0.05). The best PI was obtained with T50-0 in growing phase. FAP improved PI only in growing phase and ENZ combined with FAP showed variant PI. Results showed that FAP may be considered as a suitable option for feeding pigs because it maintains animal productivity.